2017
DOI: 10.4314/njb.v32i1.11
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Lipase from <i>Aspergillus flavus</i> PW2961 using Magnetic Nanoparticles.

Abstract: Lipase from Aspergillus flavus was purified in a single step purification using MnFeO 4 magnetic nano particles to achieve a 20.53-fold purification with specific activity of 11.29 U/mg and a 59% recovery yield. SDS-PAGE of lipase showed a single pure band with corresponding molecular weight of 35 kDa. The optimal temperature and pH for the enzyme activity were 45°C and 7.0 respectively. Addition of olive oil (1 %w/v) enhanced pH stability of the lipase with 86% residual activity at pH 7.0 after 6 h of incubat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…It alters the conformation of the active site resulting in a declining substrate-enzyme contact [40]. Like our findings, Thamaraichelvan et al [41] and Kareem et al [42] reported 45 °C as the optimal temperature for A. niger and A. flavus lipases, respectively. The temperatures optimum of P. fellutanum lipase were also coherent with P. verrucosum lipase that exhibited the highest catalytic activity at 42 °C [43].…”
Section: Lipase Activity At Varying Temperatures and Activation Energysupporting
confidence: 80%
See 1 more Smart Citation
“…It alters the conformation of the active site resulting in a declining substrate-enzyme contact [40]. Like our findings, Thamaraichelvan et al [41] and Kareem et al [42] reported 45 °C as the optimal temperature for A. niger and A. flavus lipases, respectively. The temperatures optimum of P. fellutanum lipase were also coherent with P. verrucosum lipase that exhibited the highest catalytic activity at 42 °C [43].…”
Section: Lipase Activity At Varying Temperatures and Activation Energysupporting
confidence: 80%
“…[41] and Kareem et al. [42] reported 45 °C as the optimal temperature for A. niger and A. flavus lipases, respectively. The temperatures optimum of P. fellutanum lipase were also coherent with P. verrucosum lipase that exhibited the highest catalytic activity at 42 °C [43].…”
Section: Resultsmentioning
confidence: 99%
“…A further increase in pH beyond 7.5 presented a declining trend in enzyme activity, indicating the neutral character of A. melleus lipase. Kareem et al 33 reported that lipase from A. flavus PW2961 presented activity over a wide pH range (5)(6)(7)(8)(9), with an optimal activity at pH 7.0. Likewise, the optimal activities of lipases produced by two species of Aspergillus performed best at pH 6.0.…”
Section: Resultsmentioning
confidence: 99%
“…Lipase from Aspergillus flavus PW2961 was thermostable at temperature 40, 50, and 60°C by retaining 91, 86, and 79% residual activity, respectively, after 4 h incubation [48]. Cold adaptive lipase from Staphylococcus lipolyticus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Purified lipase from Y. lipolytica retained 95 and 83% of its original activity for 4 h at 30 and 35 °C, respectively, but only 32 and 5% of the activity was left when it was incubated for 4 h at 40 and 45 °C, respectively . Lipase from Aspergillus flavus PW2961 was thermostable at temperature 40, 50, and 60 °C by retaining 91, 86, and 79% residual activity, respectively, after 4 h incubation . Cold adaptive lipase from Staphylococcus lipolyticus sp.…”
Section: Discussionmentioning
confidence: 99%